Spiritual Well-Being in Coronary Heart Disease Patients: A Scoping Review - Huda, Nur (Journal of religion and health, 2026)
Coronary Heart Disease (CHD) is one of the leading causes of death worldwide and has multidimensional impacts, including physical, psychological, social, and spiritual aspects. Spiritual well-being (SWB), which encompasses religious and existential dimensions, is crucial in helping patients cope with the disease. However, its role in CHD patients has not been comprehensively mapped. This scoping review explores the concept of spiritual well-being, its dimensions, and its impact on CHD patients. This scoping review uses the Arksey and O'Malley framework and the PRISMA-ScR guidelines. Literature searches were conducted using the Scopus, ScienceDirect, PubMed, Springer, and ProQuest databases with keywords related to CHD and SWB. Inclusion criteria included original articles in English, full text, published between 2014 and 2025, and examining SWB in CHD patients. Of the 1,698 articles identified, eleven articles met the criteria for analysis. Most of the studies originated from Iran, followed by Turkey, Indonesia, and Brazil. The results showed that high spiritual well-being was associated with reduced anxiety, depression, and fear of death; lower severity of coronary heart disease; and improved quality of life. Spiritual well-being plays a crucial role in improving psychological aspects, promoting healthy lifestyle behaviors, and improving the quality of life in patients with coronary heart disease.